ANALISIS KEBERMANFAATAN WEBSITE SEKOLAH TINGGI PARIWISATA (STIPAR) TRIATMA JAYA MENGGUNAKAN METODE USABILITY TESTING - Indriyani, Ni Luh Putu Ratih; Dantes, Gede Rasben; Aryanto, Kadek Yota Ernanda (International Journal of Natural Science and Engineering, 2017)
This research is aimed to determine the results of the usability analysis from the website Sekolah Tinggi Pariwisata (STIPAR) Triatma Jaya viewed from the user side as well as knowing the recommendation of website improvement of Sekolah Tinggi Pariwisata (STIPAR) Triatma Jaya from usability aspect. The methods used are Usability Testing of Performance Measurement and Retrospective Think Aloud (RTA) techniques and the dissemination of SUS questionnaires.Â The results showed that the Sekolah Tinggi Pariwisata (STIPAR) Triatma Jaya still not effective, it is seen from the error or mistake made by users of lecturers and students while doing the task. Statistically website Sekolah Tinggi Pariwisata (STIPAR) Triatma Jaya has been efficient for lecture but not efficient for college students users. For lecturers there are 6 out of 10 tasks that do not have significant time difference, while forÂ college students there are 4 out of 10 tasks that do not have significant time difference. From the aspect of user satisfaction, both lecturers and college students feel still less satisfied using the website of Sekolah Tinggi Pariwisata (STIPAR) Triatma Jaya, this can be seen from the SUS questionnaire scores of lecturers of 63.28 and college students users of 58.44. Based on the analysis result, it can be concluded that the Sekolah Tinggi Pariwisata (STIPAR) Triatma Jaya has not fulfilled the criteria of products that have good usability, because the three aspects (effectiveness, efficiency and user satisfaction) have not been met. Based on the above, the recommendation of Sekolah Tinggi Pariwisata (STIPAR) Triatma Jaya website is focused on adjustment of display, language and term change, feature addition, menu name adjustment, menu structure and menu layout, content addition and menu simplification. Repairs done by making wireframe recommendation page Sekolah Tinggi Pariwisata (STIPAR) Triatma Jaya.